Biaya Operasional Reksadana Sebagai Interverning Pengaruh Karakteristik Reksadana Terhadap Kinerja Reksadana Saham Di Indonesia - Harjono, Timotius Hans; Susilawati, Cicilia Erna; Prabowo, F.X. Agus Joko Waluyo (Kajian Ilmiah Mahasiswa Manajemen, 2017)
This study examines the impact of fund characteristics on the performance of mutual fund through expense ratio as a mediation variable. This research used mutual fund that registered in Indonesia with period of research 2015-2016 and amount of 71 samples. The result found that mutual fund portofolio turnover has a positive impact on fund performance. In addition, total assets of mutual fund have a negative impact on fund expenses and portofolio turnover have a positive impact on expense ratio. The results of this study also found that expense ratio doesn’t mediate fund characteristics and fund performance because expense ratio have no significant impact on the performance of mutual fund. Implication of this research is investor in Indonesia do not focus on mutual fund expenses, they are more concerned about security on their investment and the performance of the mutual funds. However, this make investment managers less focused on mutual fund expenses and more focused on maximizing the performance of the mutual funds by trading them.